Workshop Variabel Intervening dengan Olahan Data Primer Menggunakan Amos dan Data Sekunder Menggunakan Stata, Implikasi Riset Akuntansi Pada PDIE Konsentrasi Akuntansi, Universitas Trisakti - Tambun, Sihar; Sitorus, Riris Rotua (Universitas 17 Agustus 1945 Jakarta, 2025)
The workshop aimed to improve students' understanding of the concept of intervening variables in a research model. Furthermore, students were targeted to be able to independently process accounting research data for research models that have intervening variables, both for panel data and survey data with questionnaires. Data processing was taught using Stata and Amos software. The methods used in this workshop were lecture and practical methods. Lectures were used to explain the concepts theoretically. Practicals were conducted simultaneously and guided by resource persons. Evaluation results showed that the majority of participants had a good understanding of the material, with the majority of participants being able to independently process accounting research data, for intervening models, using both Stata and Amos software. This workshop recommended that the concept of intervening variables be studied continuously, and the use of software for data processing should be continuously practiced to become more familiar and able to independently process accounting research data.